Comparative Test Of Effectiveness Between Lotus (Nymphaea Firecrest) And Water Hyacinth (Eichhornia Crassipes) To Reduce Tofu Wastewater Pollutants - Muliyadi Muliyadi (Jurnal Kesehatan Prima, 2020)
Tofu industrial liquid waste is waste generated in the process of making tofu or when washing soybeans. In Ternate City, North Maluku, tofu waste is generally discharged into the sea; this causes environmental pollution. This study aims to compare the effectiveness of lotus (Nymphaea Firecrest) and water hyacinth (Eichhornia Crassipes) to reduce levels of pollutants TDS (Total Dissolved Solids) and TSS (Total Suspended Solid) in tofu wastewater in the Tofu Industry in Jambula Village by "phytoremediation process." The research method used in this study is the Experiment Method. The sample total used is 30 liters. From the results of this study indicate that the results of the first examination for water hyacinth, TDS 525mg / l and TSS 449mg / l and lotus, TDS 598 mg / l and TSS 421mg / l, for the second examination for water hyacinth, TDS 445mg / l, and TSS 330mg / l and for lotus, TDS 598 mg / l, and TSS 421mg / l, and for the third examination of water hyacinth, TDS 720mg / l, and TSS 311mg / l and for lotus, TDS 600mg / l and TSS 419mg / l. It can conclude that the most effective way to reduce TSS (Total Suspended Solid) and TDS (Total Dissolved Solids) content is by using Water Hyacinth